Educators’ role in promoting children’s thinking skills in the context of meaningful play experiences - Badzis, Mastura (2014)
Play is regarded as the appropriate and agreed approach in enhancing children’s learning development. However, there has been surprisingly little research on the ways in which educators actually understand and facilitate play. This study investigates the experiences and practices of four (4) Pusat Anak Permata Negara (PAPN) educators regarding play as a vehicle to promote children’s creativity and enhance children’s thinking skills. The focus of this study was on the play criteria practiced by the educators and the practices as well as the roles undertaken by the educators during play time. This study used a pure qualitative methodology.The data was collected by utilizing direct observation sheets during the children’s play activities and semi-structured interviews with the educators. Results from the four series of observations revealed thatplay activities tended not to enhance children’s thinking skills and creativity in the context of meaningful play experiences in all four settings.The educators tend to take a more didactic role; whileresults from the interviews supported that the educators have vague understanding on the notion of their role in promoting children’s creativity and thinking skills